2015
DOI: 10.1007/s11192-015-1658-7
|View full text |Cite
|
Sign up to set email alerts
|

Keywords co-occurrence mapping knowledge domain research base on the theory of Big Data in oil and gas industry

Abstract: Taking the theses' keywords in China from 1986 to 2014 as the research materials, use the basis concept of the Big Data Theory to further study the keywords which related to oil and gas industry. Analyze the keywords frequency of the theses in oil and gas industry and its co-occurrence frequency pair, and then use the theory of mapping knowledge domain to visualize the keywords co-occurrence network in petroleum industry so as to make further research of the heated issues that mapping knowledge domain has show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…To address such a gap, we propose a bibliometric study that covers the years from 1985 to 2015. In fact, bibliometric studies have shown their usefulness in a broad range of fields such as management (Podsakoff et al, 2008), entrepreneurship (Landström et al, 2012;Marzi et al, 2017a;2017b), expatriates , corporate social responsibilities , supply chain ( Gonzalez-Loureiro, et al, 2015), operations management (Hsieh & Chang, 2009;Zhu et al, 2015), and innovation (Fagerberg et al, 2012;Appio et al, 2016) by helping scholars to sort the streams of research from the "tangled forest" of the scientific proliferation. Thus, the data collected in this paper covers thirty years of research in such a field allowing scholars to have a wider picture of the knowledge base created.…”
Section: Introductionmentioning
confidence: 99%
“…To address such a gap, we propose a bibliometric study that covers the years from 1985 to 2015. In fact, bibliometric studies have shown their usefulness in a broad range of fields such as management (Podsakoff et al, 2008), entrepreneurship (Landström et al, 2012;Marzi et al, 2017a;2017b), expatriates , corporate social responsibilities , supply chain ( Gonzalez-Loureiro, et al, 2015), operations management (Hsieh & Chang, 2009;Zhu et al, 2015), and innovation (Fagerberg et al, 2012;Appio et al, 2016) by helping scholars to sort the streams of research from the "tangled forest" of the scientific proliferation. Thus, the data collected in this paper covers thirty years of research in such a field allowing scholars to have a wider picture of the knowledge base created.…”
Section: Introductionmentioning
confidence: 99%
“…It includes the deployment of other advanced IT tools such as big data(Perrons and Jensen, 2015), cloud computing(Perrons and Hems, 2013) and etc. Quoniam, 2013);(Chelmis et al, 2013);(Han et al,2014);(He and Wang, 2015);(Kim et al, 2014);(Perrons and Hems, 2013);(Perrons and Jensen, 2015); (Popa and Cassidy, 2012)*;(Sawaryn et al, 2014);(Veyber et al, 2012);(Ward et al, 2014)*;(Zhu et al, 2015) (Aveva, 2015a); (Aveva, 2015c);(Aveva, 2015, p.26-30);(Aveva, 2015, p.31- 33);(Aveva, 2015, p.34-37);(Aveva, 2015, p.42-45);(Aveva, 2015, p.46-47);…”
mentioning
confidence: 99%
“…Co-citation analysis identifies the rate in which the same documents are repeatedly cited together by other sources (Benckendorff and Zehrer, 2013). A co-occurrence of keywords analysis is also done to examine the relationship and frequency of keywords within the domain based on authors (Zhu et al , 2015). This technique highlights current research themes in the development of smart tourism research, which is needed to address research question three.…”
Section: Methodsmentioning
confidence: 99%